Chinese Colorless HPHT Synthetic Diamond Inclusion Features and Identification - Ying Ma; Zhili Qiu; Xiaoqin Deng; Ting Ding; Huihuang Li; Taijin Lu; Zhonghua Song; Wenfang Zhu; Jinlin Wu (Crystals, 2022)
Chinese HPHT diamonds have improved dramatically in recent years. However, this brings a challenge in identifying type IIa colorless diamonds. In this study, eleven HPHT and three natural, colorless, gem-quality IIa diamonds were analyzed using magnified observation, Raman, PL and chemical element analysis. The results show that only HPHT samples possessed kite-like inclusions and lichenoid inclusions, as verified by their complex Raman spectra (100–750 cm−1). Through PL mapping, HPHT and natural IIa diamonds were distinguished by their growth environments, which were reflected by PL peaks at 503, 505, 575, 637, 693, 694 and 737 nm. The chemical components of HPHT IIa diamond carbide inclusions are mainly Fe, Co, Ni and Mn, but those of Natural IIa are mainly Fe and Ni. As a result, the chemical components can be used to distinguish a natural colorless IIa diamond from a synthetic diamond.